ANALISIS BEBAN KERJA MENGGUNAKAN METODE FULL TIME EQUIVALENT (FTE) UNTUK MENGOPTIMALKAN JUMLAH TENAGA KERJA DIVISI SERVICE PT. XYZ - Teddy Rizki Saputra (2023)
PT. XYZ is a heavy equipment distributor company in Indonesia. The scope of this research is focused on the Service Division of PT. XYZ. The reason for choosing the Services Division as the object of this research is that there has been no previous measurement of workforce productivity in that division, making it difficult to determine whether the workforce is productive or not. Therefore, measurement of workload is needed as a basis for calculating workforce requirements. In this study, researchers used the Full Time Equivalent (FTE) method. After the results of the FTE calculation for each position obtained by the Service Division of PT. XYZ, it is known that from a total of 30 workers in the Service Division of PT. XYZ of which there are 10 workers in the overload category, 19 workers in the normal (fit) workload category, and 1 worker in the underload category. From the results obtained, an additional workforce of 3 is needed and job distribution is carried out which aims to make the workload more even.